Extraction of trans-Anethole from Star Anise (Illicium verum) Using Combination of Microwave, Ultrasonic, and Enzyme Assisted Methods and Evaluation of Their Antibacterial Activity - Elvina Dhiaul Iftitah; Warsito Warsito; Vivi Nurhadianty; Fitri Ariadna Sodi Miranda; Rafika Nur Hafidah (Universitas Gadjah Mada, 2024)
This study examines the efficiency of non-conventional extraction methods to obtain trans-anethole from Illicium verum using single and combination extraction techniques: microwave assisted extraction (MAE), ultrasound-assisted extraction (UAE), and enzyme assisted extraction (EAE) employing lipase from Aspergillus oryzae. All extraction methods were conducted using 96% ethanol (1:5 w/v) with varying time durations. The resulting product was an oleoresin, subsequently analyzed and separated using thin liquid chromatography (TLC) and column chromatography employing a solvent mixture of toluene and ethyl acetate in a 9:1 ratio and identified via gas chromatography-mass spectra (GC-MS). The results revealed that trans-anethole yields from a single extraction method were 30.76% (MAE), 41.05% (UAE), and 40.90% (EAE). The combination of extraction methods, such as MAE-UAE, MAE-EAE, and UAE-EAE, produced trans-anethole yields of approximately 42.73%, 52.80%, and 45.02% respectively, surpassing the yields of the single extraction method. Notably, the triple extraction method of MAE-UAE-EAE yielded the highest trans-anethole content at 56.00%. Antibacterial testing against Staphylococcus aureus was performed on all samples. The trans-anethole demonstrating the highest inhibitory effect was obtained from the double extraction method, particularly the combination of UAE-EAE. These results underscore the synergistic efficiency of combining microwave, ultrasound, and enzymatic extraction methods, highlighting their superior efficacy in obtaining trans-anethole.